Supersymmetric-charged-Higgs-boson production at the Superconducting Super Collider - Eboli, O. J.P.; Marques, G. C.; Novaes, S. F.; Natale, A. A.; Pulido, J. M.R. (American Physical Society (APS), 1988)
We analyze the production of supersymmetric charged Higgs bosons via vector-boson fusion at Superconducting Super Collider energies. This process leads to a measurable cross section only for a very limited range of masses of &300 400 GeV &>40 GeV. © 1988 The American Physical Society.